Listening Skills of Elementary School Students: A Bibliometric Analysis and Systematic Literature Review: Keterampilan Menyimak Peserta Didik Sekolah Dasar: Bibliometric Analysis Dan Systematic Literature Review - Hasna Zhafira; Mela Darmayanti (Universitas Negeri Surabaya, 2026)
Listening skills are one of the four most important language skills. This study aims to map the development of research on listening skills in elementary school students from 2015 to 2025 through a bibliometric approach and a systematic literature review. Data was obtained from Google Scholar using the Publish or Perish application with the PRISMA selection technique, resulting in 42 articles that met the criteria. Bibliometric analysis was conducted using VOSviewer to identify publication trends, subtopic density, productive authors, most cited articles, and dominant journals. The research findings indicate that the main focus of the study is on listening skills and learning media, with a dominance of audio-visual and video media usage. Factors affecting listening skills learning problems include internal and external aspects. Additionally, eight learning models, two teaching methods, and seven digital and four non-digital media were found to be effective in improving listening skills. This finding provides a comprehensive overview of research directions and serves as the basis for developing listening comprehension instruction in elementary schools.